The Role Of Youth In The Implementation Of Kotaku Program In Langsa City - Raja Syahputra; Suwardi Lubis; Sakhyan Asmara (International Journal of Science, Technology & Management, 2021)
This study aims to determine the role of youth in the implementation of the KOTAKU program in Langsa City, to determine the factors that encourage and hinder youth in implementing the KOTAKU program in Langsa City. The analytical method used in this research is a qualitative descriptive analysis method by looking at the role of youth and inhibiting and supporting factors in the activities of the KOTAKU program in Langsa City. This research was conducted in Langsa City by using a sample in several areas in Langsa City that have implemented KOTAKU program activities. The results of research on youth in Langsa City play an active role in the KOTAKU program activities in Langsa City. The driving factor for the KOTAKU program activities is the participation of youth and communities who want their living areas to be free from slum settlements. Meanwhile, the inhibiting factor is the lack of public understanding of the KOTAKU program and the lack of public awareness in maintaining the infrastructure, facilities and infrastructure resulting from the KOTAKU program activities in Langsa City.